Estimating software projects’ effort, time, and cost using function point analysis and analogy-based effort estimation - Tuazon, John Byron D. (Animo Repository, 2018)
The success or failure of a software development project heavily relies on the ability of the software development team to anticipate all the necessary scope and requirements at the earliest possible time. Typically, project success is measured based on the ability to deliver a product that fulfills the “iron triangle” which are the scope, time, and cost without sacrificing quality. Software effort estimation continues to gain popularity among industry and academic practitioners as estimating the needed effort in completing a software project is seen necessary as most software projects fail because of inaccurate time and cost estimation which are both derived from effort. This study shall use function point analysis and analogy-based effort estimation model to accurately predict the necessary effort for a new software project based on the historical project data. Result shall be checked using standard performance measures to ensure that estimates are accurate. Similarities of past related software project shall be measured based on Euclidean distances using the adjusted function points, unadjusted function points based on complexity, and non-functional requirements as the main effort drivers to derive the closest analogous software project. Reports like the work breakdown structure and responsibility assignment matrices (h, $, t) shall also be produced by developing a tool thus making this study unique and novel compared to other academic paper of the same domain.